Towards an emissions trading scheme for air pollutants in India: A concept note-Key components of an emissions traing scheme: MoEF Discussion paper, Ministry of Environment & Forests, Government India, New Delhi - Duflo Esther etal (2010)
Articles bound received from Dr. James Jacob, Director, March 2021